أصناف الترقية في الوظيفة العمومية - بطاط ايناس -تلويت شيماء (جامعة المسيلة, 2024)
The aim of this study is to clarify the subject of promotion in the civil service and its legal framework. This study relies on two approaches: the descriptive approach, by studying the concept of promotion in the civil service, as well as examining its types and criteria; and the analytical approach, by analyzing the legal texts related to promotion in the civil service. Thus, one of the key factors for an employee's success in their work is promotion, as it serves as an incentive to develop their skills and excel in their work, while also providing material and moral benefits. This promotion is carried out according to specific criteria: promotion by seniority, promotion by merit, and promotion by both seniority and merit. Promotion is divided into grade promotion and rank promotion, according to conditions and procedures stipulated in various legislations and legal texts.